Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion